Studi Potensi Likuifaksi Timbunan Pasir Dengan Gradasi Ukuran Butiran Di Atas Tanah Lunak - Putra Hasibuan; Agus Ika Putra; S A Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The island of Sumatra is the region with the highest quake intensity. Earthquakes in Aceh, Nias, Mentawai, and Padang caused a wave of vibration in the surrounding area. In Pekanbaru many buildings are built on peat soil with sand as an embankment. Liquefaction potentially occur in the earthquake propagation zone. Liquefaction is the transformation of soil state from solid to liquid. Liquefaction potential can be analyzed based on field test and laboratory test. Laboratory test was conducted using a one-way shaking table. Vibrating table moves in a horizontal and opposite direction in a vertical direction. The acceleration variations used are 0.25g and 0.32g. Peat soil thickness used 10 cm. Sand embankment thickness used 15 cm with gradation variation and water level as high as embankment thickness. Distributed load used 40kg/m2. Evaluation of liquefaction potential by analyzing soil surface settlement observation, excess pore water pressure and effective vertical stress. The measurement of pore water pressure was measured using 0.5 mm diameter glass pipe. Soil settlement measured by using ruler. The results of the test show that along with increasing acceleration, the bigger soil settlement and pore water increment will be. Grain size is very influential on the occurrence of liquefaction potential. The test results shows that the fine graded sand had maximum settlement and excess pore water pressure so that itnhas the most extreme effective vertical stress. Well graded sand tends to stable but on 0,32g acceleration it has effective vertical stress value less than zero.Keywords : liquefaction, excess pore water pressure, shaking table, grain size